On What We Have Learned and Still Need to Learn about the Psychosocial Impacts of Genetic Testing - Parens, Erik (The Hastings Center report, 2019)
Since the start of the program to investigate the ethical, legal, and social implications (ELSI) of the Human Genome Project in 1990, many ELSI scholars have maintained that genetic testing should be used with caution because of the potential for negative psychosocial effects associated with receiving genetic information. More recently, though, some ELSI scholars have produced evidence suggesting that the original ELSI concerns were unfounded, exaggerated, or, at a minimum, misdirected. At least in the contexts that have been most studied, large negative impacts have not been found in the vast majority of people studied. What might explain the discrepancy between the original hypothesized outcomes and the growing impression that large negative effects appear to be few and far between? And if the original predictions of large negative psychosocial effects were simply wrong, is it time for ELSI researchers to move on? Should genetic testing be routinized, and would it be appropriate to relax or abandon the practice of engaging patients in a process of detailed informed consent before they receive genetic information? To confront those questions, we convened a conference entitled “Looking for the Psychosocial Impacts of Genomic Information” to review what is known about the negative impacts of genetic information on a variety of populations and in multiple medical and social contexts, to explore the implications of the findings, and to consider whether future research might benefit from different methods than have been used to date.